"Palmas para mulheres mil" em comunidades Quilombolas: a participação do IFPR – Câmpus Palmas no programa nacional de inclusão social - Lagos, Marcia Beraldo (2014)
This thesis aims to analyze the participation of the Federal Institute of Paraná - Campus Palmas in a program of social inclusion through an extension project, titled Palmas para Mulheres Mil, which proposes better educational and professional qualifications for the participants. This extension project has his actions endorsed by the public policy "Programa Nacional Mulheres Mil", with a gender perspective, which aims, among others objectives, to promote the educational, social and productive inclusion of women in vulnerable situations. The research is characterized as documentary and exploratory. We used official documents of Mulheres Mil National Program, official documents of IFPR and Quilombola Community. For data collection we used questionnaires prepared by the project coordination, filled during the preregistration by the participants, assessment questionnaire at the end of the project, prepared by the researcher, and semi structured interviews for graduating students with the aim of characterizing their profile and educational issues, as well as the personal and professional impacts of the project in their lives. We also used semi structured interviews with the General Manager and Managers of Teaching, Research and Extension of IFPR - Campus Palmas. With the aim of investigating how was the participation of the Federal Institute of Paraná - Campus Palmas and the development of that project interview with the coordination of the extension project, in order to analyze the development of the project and its contribution to the institution; and interviews with teachers who have developed activities in the project in order to reflect on the teaching practice on a training course and qualification facing women in conditions of social vulnerability. Thus, a theoretical review of the main categories listed was performed: Public policy, Public policy with a gender perspective, University extension and Quilombola that supported this research, followed by the presentation of results. The results obtained in this research indicate that actions carried out in this project achieved some desired goals, however failed to realize fully its initial proposal, how high education and entry into the labor market of most students, but the self-esteem of students provided by the project opened the doors of the right to dream of better days.